ILLOCUTIONARY ACTS BY THE MAIN CHARACTER IN A STAR IS BORN MOVIE - Sataruno, Noveren; Olii, Sanerita T.; Andries, Fivy A. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
The study’s goals are to identify the illocutionary acts in "A Star Is Born," as well as to interpret and explain the function of those utterances. This research involves qualitative methods. The researchers collected data by watching the movie, marking the types of Illocutionary Acts identified as Representative, Directive, Commissive, Expressive, Declarative, and interpreting the meaning of those. Searle classifications are used to categorise the data. This study employs the three steps proposed by Miles and Huberman for data analysis: data reduction, data display, and data verification/conclusion. This study’s findings reveal a total of 50 speech acts delivered by the main character in the film A Star Is Born. This study is intended to serve as a resource for readers and other researchers interested in learning and interpreting Illocutionary Acts in films or other literary works.